The Value and Character Building Education in Folklore from Bataknese "Sigale-Gale" - Ria Anita Sipahutar; Remlina Wati Sianturi; Yenita Sembiring (Journal of Languages and Language Teaching, 2021)
Education is the learning of knowledge, the skills of every person that are passed down from generation to generation for one generation. But in education, it is also essential to learn the formation of good character. In this relevant research, especially those that raise Folklore as the object of study, only a few people know about it. Folklore is a medium that can use as a means of forming positive characters in children through moral values and character education contained in the story. This type of research is qualitative descriptive obtained, analyzed, and analyzed in writing to describe the moral values and character building contained in the Toba Batak folklore "Sigale-gale." Data collection was carried out by reading the Sigale-gale folklore text repeatedly and identifying the data in the form of keywords related to the values forming the characters in the story. Furthermore, the collected data were analyzed using content analysis techniques. The results showed that there were four character-forming values in the Sigale-gale Folklore; namely hard work, curious, friendly, and wise.